2019
DOI: 10.1002/mgg3.972
|View full text |Cite
|
Sign up to set email alerts
|

New insights into genetic variant spectrum and genotype–phenotype correlations of Rubinstein‐Taybi syndrome in 39 CREBBP‐positive patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. Abstract Background: Rubinstein-Taybi syndrome (RSTS) is a rare congenital disorder characterized by broad thumbs and halluces, intellectual disability, distinctive facial features, and growth retardation. Clinical manifestations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 33 publications
5
29
1
1
Order By: Relevance
“…The most common clinical finding in our entire cohort was broad thumbs and/or halluces, angulated or not, present in an average of 97% of individuals. This is consistent with the medical literature (Hennekam, 2006; Pérez‐Grijalba et al, 2019; Schorry et al, 2008). Interestingly, we identified three clinical features that significantly differ across population groups: (a) grimacing smile ( p < .002) and (b) eye abnormalities ( p < .03), which were both observed more frequently in Latin Americans and Asians, and (c) hirsutism ( p < .04) which was seen more frequently in Latin Americans and Middle Easterners.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The most common clinical finding in our entire cohort was broad thumbs and/or halluces, angulated or not, present in an average of 97% of individuals. This is consistent with the medical literature (Hennekam, 2006; Pérez‐Grijalba et al, 2019; Schorry et al, 2008). Interestingly, we identified three clinical features that significantly differ across population groups: (a) grimacing smile ( p < .002) and (b) eye abnormalities ( p < .03), which were both observed more frequently in Latin Americans and Asians, and (c) hirsutism ( p < .04) which was seen more frequently in Latin Americans and Middle Easterners.…”
Section: Discussionsupporting
confidence: 92%
“…Eyes abnormalities included strabismus (8/35), glaucoma (3/35), refraction errors (3/35), nasolacrimal duct obstruction (2/35), cataract (2/35), iris coloboma (1), sclerocornea (1), and hypopigmented retina (1). When excluding intellectual disability, comparison of 21 phenotypic features between our cohort and two previous RSTS studies (Fergelot et al, 2016; Pérez‐Grijalba et al, 2019) showed that the most common features found in both the present study and one of the two previous studies are broad thumbs and halluces. However, we noted some variations in the frequency of clinical features across studies, more manifest between the study by Fergelot et al and our cohort (Table 1).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…RSTS is a rare autosomal dominant inheritance disease with an estimated prevalence of 1:125.000 in live births [2] . The main clinical presentations are congenital multi-system abnormalities such as growth retardation, intellectual disability, microcephaly, broad thumbs and halluces, distinctive facial features, tumor [3][4] . Currently, The diagnosis rate and clinical presentations of RSTS are rare.…”
Section: Introductionmentioning
confidence: 99%